The Role of the ISSAI 20 Transparency and Accountability Standard in Narrowing the Quality Gap in the Performance Supreme Audit Institution - Mohammed Falah Hassan; Sabeha Barazan Al-Obeidi (Journal of Madenat Alelem University College, 2020)
The supervisory work is a sophisticated and advanced method that has evolved with the passage of times and times to cope with the financial crises facing countries. It is also the safety valve that guarantees the implementation of the business and the achievement of the goals set for the countries and institutions and has become consistent with them to reduce the mistakes and deviations and the possibility of correcting these errors The supervisory bodies are the most important bodies that carry out this work because they have the right to carry out financial, administrative and legal control over the work of the executive body and to report to the highest authority in the state represented by parliaments or The executive authority. This research aims at measuring the compliance of the Federal Audit Bureau with applying the transparency and accountability standard for INTOSAI and identifying the gap in transparency and thus narrowing the gap. The research reached a number of conclusions, the most important of which is the failure of the SAI to publish the financial statements of the organization, including the use of the funds at its disposal, The financial statements and the reports of the Authority shall be subject to inspection by the legislative authority in accordance with the requirements of INTOSAI standards and poor communication with the media or any other concerned parties about its operations and the results of its supervision and to ensure that it is visible in the field. The research has reached a number of recommendations, the most important of which is the adoption of the international standards of the Supreme Audit Institutions (INTOSAI) from the Federal Audit Bureau in accordance with a predefined work plan. The Federal Audit Bureau is a member of INTOSAI, in addition to providing summaries of monitoring reports in a language In addition to its national languages ​​and work on translating summaries of reports into English.